Wolbachia endosymbiont in a species of the Anastrepha fraterculus complex (Diptera: Tephritidae) - Selivon, Denise; Perondini, André Luiz P.; Ribeiro, Alberto F.; Marino, Celso L. [UNESP]; Lima, Marleide M.A. [UNESP]; Coscrato, Virginia E. [UNESP] (Taylor & Francis, 2002)
In Anastrepha sp.2 aff. fraterculus, the egg-cell harbours a large population of endosymbionts. The bacteria were identified as belonging to genus Wolbachia by PCR assay using primers of the ftsZ gene followed by sequencing of the amplified band. Newly deposited eggs stained in toto by Hoechst show that the bacteria are unevenly dispersed throughout the egg-cell, with a higher accumulation at the posterior pole, and that the degree of infestation varies from egg to egg. Analysis by transmission electron microscopy shows that bacteria are present in the female germ line of embryonic and larval stages, as well as in the different cell types of the ovaries at the adult stage. Mature ova within the follicles harbour a large population of the symbionts. The results indicate the existence of a transovarian transmission of the endosymbionts in this fly.
Keywords: Bacteria; Eggs; Embryo; Fruit flies; fstZ gene; Ovaries; Anastrepha; Anastrepha fraterculus; Bacteria (microorganisms); Diptera; Drosophila melanogaster; Tephritidae; Wolbachia